GAMBARAN MANFAAT PROGRAM FAMILY DEVELOPMENT SESSION KEMENTERIAN SOSIAL REPUBLIK INDONESIA - Wulandari, Tyas; Hakim, Lukman Nul (Jurnal Aspirasi, 2015)
As an effort to protect Indonesian children, the State has made the Minister of Social Affairs Regulation No. 21 of 2013 on Child Care and Act No. 35 of 2014 on Child Protection. To optimize the child protection efforts, Ministry of Social Affairs seeks to make the program of Family Development Session (FDS) with the purpose to built the knowledge of parenting for Indonesian parents to supports the development and protection of children. This study seeks to see the benefits of the implementation of the FDS program. The research uses qualitative methods. The technique used to collect data is interview and observations of the three informants. The results showed that the FDS program has succeeded in changing the informants parenting style in all three domains, namely affective, behavior, and cognitive. In the future, the government should ensure that the FDS program is felt by all the people of Indonesia. While the Parliament should encourage the government to be more creative and innovative to make Indonesian children healthy in spiritual and body owing, to the proper parenting and proper protection.